The Development of Comic Learning Media on The Human Respiratory System Topic to Facilitate Student Health Literacy - Sholahudin, N. P.; Agustin, R. R.; Rochintaniawati, D. (Journal of Science Education Research, 2025)
Basic Health Research (Riskesdas) and the Global Youth Tobacco Survey (GYTS) identify an increase in the prevalence of smokers among teenagers, indicating low health literacy among junior high school students. To address this, interactive learning media were developed to facilitate student health literacy. This research focused on developing comics as a learning medium for the respiratory system to facilitate health literacy. It was a developmental research method using the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The developed comic was validated by three experts using an expert judgment rubric. Data were collected from 34 students in 8th grade and four science teachers through questionnaires. Expert validation data were analyzed using Aiken's V formula, while questionnaires were analyzed by calculating the percentage of agreement. Expert judgment validation received a score of 0.88, indicating high validity. The questionnaire results showed a high percentage of agreement: 96.57% from students and 95.83% from teachers. These findings suggest that comics are highly effective as learning media for the respiratory system topic and effectively support students' health literacy efforts.